Identification of Formal-Post Formal Reasoning Prospective Biology Teachers on Three Aspects of Courses - Aa Juhanda*; Nuryani Y. Rustaman; Topik Hidayat; Ana Ratna Wulan (Universitas Syiah Kuala, 2021)
This descriptive study aims to determine the reasoning of the formal-post formal operations of biology teacher candidates in three aspects of lectures. The research sample consisted of 76 students who took part in the 2019/2020 academic year lectures which were taken using the purposive technique. The sample consisted of 29 students in the General Biology practicum subject, 24 students in the invertebrates practicum subject, and 23 students in the vertebrate zoology practicum subject. The data was collected through a test technique using formal-post-formal operational reasoning questions that were developed by themselves and had met the constructive and empirical valid criteria. Data analysis regarding the level of formal-post formal operational reasoning was carried out using the percentage correct score technique obtained for each item so that the correct score was obtained from all students. The results showed that there was a difference in the percentage level of formal-post formal operational reasoning for each level of student lectures. The highest to the lowest level of reasoning was obtained by students who took the vertebrates zoology practicum course by 67%, invertebrates zoology practicum by 67%, and general biology practicum by 17%. Also, students' formal operational reasoning in each subject tends to be lower when compared to their post-formal operational reasoning. The most common indicators of formal reasoning among the three aspects of the lecture are proportional reasoning, and indicators that are lacking are probabilistic and correlational.